Ineffective HR Practices Hamper Performance in Indonesian Hospitals: Praktik SDM yang Tidak Efektif Menghambat Kinerja Rumah Sakit di Indonesia - Dwi Tantri Widiya Sari; Nurasik Nurasik (Academia Open, 2024)
Jasem Sidoarjo General Hospital in East Java strives to provide high-quality healthcare, but its human resource management (HRM) faces significant challenges. This study examines the role of HR managers in improving hospital performance and human resource development using a descriptive qualitative method. Findings reveal that HR planning is fragmented and not aligned with organizational needs, and the selection process is inefficient due to reliance on internal referrals. Training is limited to permanent staff, and compensation fails to motivate employees adequately. Recommendations include adopting a centralized HR planning approach, implementing objective selection processes, and expanding training opportunities for all staff to enhance HRM and overall hospital performance. Highlight: HR planning is fragmented and lacks alignment with hospital needs. Employee selection relies on internal referrals, reducing efficiency. Training and compensation policies need to be more inclusive and motivating. Keywoard: Human Resource Management, Hospital Performance, Staff Development, Qualitative Research, East Java